2021
DOI: 10.1177/09593535211059003
|View full text |Cite
|
Sign up to set email alerts
|

From ignorance to knowledge: Sexual consent and queer stories

Abstract: The problem of sexual assault has received increasing public attention over the last few years, with an increasing focus on the concept of sexual consent to solve the problem. Education efforts focus on teaching people what consent is and how to explicitly communicate about sex, constructing consent as a knowledge problem. Using the stories of queer adults, this study calls for the development of an epistemology of sexual consent. I argue that the current research and scholarship fail to recognise existing kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Sanne (23/cis woman/ heteroflexible) argued that it was better "to get each other's consent to sex in a sober state", before having sex in an intoxicated state, since consent to sex in a sober state "was more reliable". Therefore, the participants seemed to draw on the notion that NSEs happen due to miscommunication, which supports the "miscommunication hypothesis" (see also Beres, 2022;Kitzinger & Frith, 1999;Maryn, 2021;O'Byrne et al, 2006O'Byrne et al, , 2008, similar to the first repertoire. On the other hand, however, alcohol intoxication was perceived as leading to a greater risk of miscommunication as the "intoxicated self" (in this case, the person at the receiving end of the sexual interaction) was viewed as less able to communicate reliable consent.…”
Section: Intoxicated Sexual Consentsupporting
confidence: 59%
See 3 more Smart Citations
“…Sanne (23/cis woman/ heteroflexible) argued that it was better "to get each other's consent to sex in a sober state", before having sex in an intoxicated state, since consent to sex in a sober state "was more reliable". Therefore, the participants seemed to draw on the notion that NSEs happen due to miscommunication, which supports the "miscommunication hypothesis" (see also Beres, 2022;Kitzinger & Frith, 1999;Maryn, 2021;O'Byrne et al, 2006O'Byrne et al, , 2008, similar to the first repertoire. On the other hand, however, alcohol intoxication was perceived as leading to a greater risk of miscommunication as the "intoxicated self" (in this case, the person at the receiving end of the sexual interaction) was viewed as less able to communicate reliable consent.…”
Section: Intoxicated Sexual Consentsupporting
confidence: 59%
“…While previous research has investigated the discourses that influence the processes of consent that resemble the repertoires found in this study, our study contributes to previous research by highlighting in what situations and with what aims and purposes young people draw on those repertoires to construct sexual consent. Our study showed that the participants drew on a neoliberal discourse (see also Beres, 2007;Loick, 2019;MacKinnon, 2016) and the miscommunication hypothesis (Beres, 2022;Kitzinger & Frith, 1999;Maryn, 2021;O'Byrne et al, 2006O'Byrne et al, , 2008 when discussing sexual consent in general and when arguing for their sexual consent communication practices. When discussing sexual consent in relation to gendered practices and expectations, many of the heterosexual participants drew on traditional masculine and feminine expectations in relation to sex and sexual consent (e.g., the "male sexual drive discourse", "women as gatekeepers, men as sexual initiators" etc.).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, shifting to a trauma-informed, anti-oppressive framework for consent education that does not rely on a binary concept opens up the possibilities for addressing persistent systemic forms of oppression that create grey areas for all youth. Notably, future research should examine the lessons for consent education from BIPOC, Two-Spirit, queer, trans and/or non-binary communities who cite a legacy of challenging binaries and refusing a normative model of consent (see Bauer 2021;Beres 2021;de Heer et al 2021). Principles of disability justice should also be incorporated into anti-oppressive, trauma-informed consent education (Wright 2021b).…”
Section: Discussionmentioning
confidence: 99%